Values and value in design - Grant R. Mills (2013)
Relatively little is known about how concepts of human values and value interact during the construction design process. Whilst researchers of value management have expounded in this context upon the complexity of the design process, problem-solving and sense-making, little is said about the alignment and reconciliation of multiple-stakeholder values and value judgements. An abductive reasoning and a grounded theory approach was adopted that iterated between literature and empirical observation to obtain new insights. The initial phase created a values and value framework and Value in Design (VALiD) approach through seven unstructured interviews, a design workshop, four Schwartz Values Surveys (with 545 participants) and 55 semi-structured interviews. The values and value parts were then separately implemented, developed and validated through action research on five live education capital projects, involving over 250 participants. Subsequently, a middle-range theory of values and value is proposed through theoretical triangulation. This draws on seven related theories to provide greater explanatory pluralism, uncover hidden phenomena and enable convergence. The research findings are significant in focusing soft value management on underlying stakeholder values and subjective value judgements. A more nuanced and intertwined relationship between stakeholder values, attitudes, behaviours and qualities during the design process is offered that promotes compromise and sense-making.